Poietic, matter and fields in the paintings of Karin Lambrecht - Cattani, Icleia (PORTO ARTE: Revista de Artes Visuais, 2013)
This essay has as its conveyer the painting of Karin Lambrecht, an artist of extensive trajectory. Her work has always dealt with painting made wi-th, besides oil paint, acrylic with dirt and other natural pigments. Her contemporary production is also characterized by blood paintings. The focus of this essay will be the analysis of relations of her poietic and her work’s poietic between the used materials and the deriving matter in pa-intings, the characteristics of different propprops and how these questi-ons altogether define works as their fields. Concepts of material imagi-nation (Bachelard) and of specific fields, expanded and out-of-the-field of painting, will be utilized. To these I add the concepts of metamorphosis and borders, to deal with the complex reality of works and questions that emerge from the painting itself.